2017
DOI: 10.1021/acs.inorgchem.7b00520
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Optical Properties of LixNa1–xBa12(BO3)7F4 Fluoride Borates with “Antizeolite” Structure

Abstract: Studied LiNaBa(BO)F (P4bc) solid solution belongs to the new class of "antizeolite" borates with [Ba(BO)] cation pattern, which contains channels filled by anionic clusters. Optical-quality crystals were grown from the compositions with different sodium-lithium ratio. The results of Rietveld refinement based on powder data demonstrate linear increase of parameter a and unit cell volume with Na/(Na + Li) ratio in cation site. Parameter c is less sensitive to the changes in stoichiometry, which is consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Both structures of the Ba 3 (BO 3 ) 1.8 F 0.6 intermediate member 29 and reported here Ba 3 (BO 3 ) 2 end-member of Ba 3 (BO 3 ) 2-x F 3x solid solution demonstrate a pronounced tetragonal pseudosymmetry, corresponding to the P4 2 /mbc space group. The potential tetragonal symmetry of Ba 3 (BO 3 ) 2-x F 3x solid solution is broken by~0.5% difference between the a and b axes of the unit cell.…”
Section: Ba 3 (Bo 3 ) 2 Structuresupporting
confidence: 65%
See 4 more Smart Citations
“…Both structures of the Ba 3 (BO 3 ) 1.8 F 0.6 intermediate member 29 and reported here Ba 3 (BO 3 ) 2 end-member of Ba 3 (BO 3 ) 2-x F 3x solid solution demonstrate a pronounced tetragonal pseudosymmetry, corresponding to the P4 2 /mbc space group. The potential tetragonal symmetry of Ba 3 (BO 3 ) 2-x F 3x solid solution is broken by~0.5% difference between the a and b axes of the unit cell.…”
Section: Ba 3 (Bo 3 ) 2 Structuresupporting
confidence: 65%
“…It was found that the ability of the [Ba 12 (BO 3 ) 6 ] 6+ cationic pattern to accommodate intrachannel assemblages is not limited by the (BO 3 ) 3− versus F − variations. We identify the same cation pattern in the Li x Na 1−x Ba 12 (BO 3 ) 7 F 4 ( P 4 2 bc ) solid solution, where channels are filled with (BO 3 ) 3− anions and (LiF 4 ) 3− and (NaF 4 ) 3− clusters . Thus, in order to exclude possible incorporation of solvent elements in the channels, we grew crystals without solvent from the composition with a slight excess of B 2 O 3 .…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations